2017
DOI: 10.1590/0102-33062017abb0121
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling plant establishment in sandy coastal systems: biotic and abiotic factors that determine Allagoptera arenaria (Arecaceae) germination

Abstract: Germination rate and establishment success of plants in harsh environments depend on the ability of seeds to withstand unfavorable environmental conditions and avoid predators. Brazilian coastal plains, known as restinga, are subject to environmental factors that seriously limit plant establishment and survival (e.g. salinity, desiccation, oligotrophy, fl ooding, high temperature and radiation levels). We tested, both in fi eld and laboratory experiments, conditions for germination and establishment of Allagop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 56 publications
(67 reference statements)
0
5
0
1
Order By: Relevance
“…() found that Morella occupies only 46% of suitable habitat (based on elevation and distance to shoreline), suggesting that the heterogeneous landscape onto which seeds disperse may not be advantageous for germination or establishment (Menezes et al. ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…() found that Morella occupies only 46% of suitable habitat (based on elevation and distance to shoreline), suggesting that the heterogeneous landscape onto which seeds disperse may not be advantageous for germination or establishment (Menezes et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Since fruit ripening of Morella coincides with the migratory season, seed dispersal may be extensive (Mabey et al 1993). Zinnert et al (2011) found that Morella occupies only 46% of suitable habitat (based on elevation and distance to shoreline), suggesting that the heterogeneous landscape onto which seeds disperse may not be advantageous for germination or establishment (Menezes et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The focus on ecological and physiological research with Allagoptera is due to the characteristics of the species A. arenaria : (i) under high temperatures they have a high germination rate (Menezes et al, 2017); (ii) as a pioneer species, it colonizes open areas favouring the entry of other species into the community (Scarano et al, 2001); (iii) by creating a microclimate conducive to germination and development of other species, it can play the role of facilitator (Menezes et al, 2017) and (iv) after the fire, it will germinate in a few days (Menezes & Araujo, 2004). Even though this species has so many characteristics that give it a high germination plasticity, no study has been carried out to investigate the properties of its fruits and seeds, which we believe should be a prime area in future research.…”
Section: Discussionmentioning
confidence: 99%
“…This contributes to increasing the genetic diversity of palm populations (Sezen et al ., 2009 ; Browne, Ottewell & Karubian, 2015 ; Browne & Karubian, 2018 a ). Long‐distance seed dispersal by frugivores that eliminate viable palm seeds has been suggested for carnivores (Gatti et al ., 2006 ; Silva et al ., 2011 ; Quintela, Iob & Artioli, 2014 ; Menezes et al ., 2018 ), fish (Anderson et al ., 2011 ) and primates (Link & De Luna, 2004 ; Link & Di Fiore, 2006 ; Canale et al ., 2016 ). Large bird species (e.g.…”
Section: Interaction Outcomes In Palm–frugivore Interactionsmentioning
confidence: 99%